KEBERADAAN SEMUT; MU’JIZAT SAINTIS AL-QUR’AN (STUDI TAFSIR SAINS SURAH AN-NAML AYAT 18-19) - Mohammad Ruslan (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2022)
In interpreting the verses of the Qur'an related to science there is still much debate, therefore, further studies are needed on the relationship between science and religion from various perspectives. This article the author wrote using a library research model and a content analysis approach. This research describes the interpretation of the scholars' interpretation of the life of ants in surah an-Naml verses 18-19. And the scientific view of the life of ants, ants are considered capable of working together to build their nests which consist of small nests, ants are animals that clone together to have effective and efficient rules that are neatly arranged.